Analisis Pengaruh Ekspor dan Impor terhadap Pertumbuhan Ekonomi di Indonesia Tahun 2012-2020 - Agustina Dian Arini; Fitriana Putri; Retno Mutia Dewi; Sri Octa Wulandari; Misfi Laili Rohmi (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This article aims to describe the impact and implications on Indonesia's economic growth from 2012 to 2020. This research is based on a literature review using a quantitative approach using secondary data obtained from the Central Statistics Agency (BPS). This research uses regression analysis, linear regression, multiple regression, with SPSS data management tools. The F test results show that exports and imports do not have a significant effect on economic growth in Indonesia. Overall, both do not have a significant impact on economic growth. All of the findings of this research highlight the importance of considering other factors that have the potential to influence Indonesia's economic growth rate. The implications of this research also provide a solid foundation for further research which may be able to explore other factors that have a greater influence on economic growth in Indonesia apart from export and import factors.